Clinical results with omni-orthocor,(r) an implantable antitachycardia pacing system. - Rothman MT; Keefe JM (Pacing & Clinical Electrophysiology, 1984)
Omni-Orthocor 234A and 239A are implantable pacers capable of synchronization with an external overdriver, Synchronous or asynchronous burst pacing, synchronized extrastimuli, or a combination of both can be obtained. Upon recognition of a tachycardia, the patient or physician can initiate pace-termination. Omni-Orthocor was implanted in 69 patients [53 for ventricular tachycardia, 11 for supraventricular tachycardia, 2 each with AV nodal reentry and WPW, and 1 patient with concealed accessory pathway). Thirty-five patients performed out of hospital termination. More resistant tachycardias were terminated in the hospital with 76.3% success in VT and only 50% success for SVT. Burst pacing was used in 75% of patients. Noninvasive electrophysiologie study was performed on all patients, and was the sole use of Omni-Orthocor in 20 patients. The device was not implicated in the six sudden death patients in this series.